2020
DOI: 10.1016/j.pmedr.2020.101171
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and subjective musculoskeletal symptoms in young male Japanese workers: A 16-year retrospective cohort study

Abstract: Highlights The SN/S and LBP risk was higher in the PL than in the GL group. Four positive predictors (life satisfaction, hours of sleep, exercise habits, physical fitness) are important factors. Health staff should advise on workers’ individual lifestyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
7
1
Order By: Relevance
“…Of the study participants, 67.1% were women and 60.6% were people aged 70 and over [14]. Because both female gender and higher age are risk factors for LBP [4,21,23], the prevalence of LBP in the LOCOMO study might be higher than that in our study. Second, the NHANES study with a nationally representative sample of the US population assessed LBP lasting almost every day for at least 3 months and reported that the prevalence of LBP in US adults aged 20-69 years old was 13.1% [23].…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Of the study participants, 67.1% were women and 60.6% were people aged 70 and over [14]. Because both female gender and higher age are risk factors for LBP [4,21,23], the prevalence of LBP in the LOCOMO study might be higher than that in our study. Second, the NHANES study with a nationally representative sample of the US population assessed LBP lasting almost every day for at least 3 months and reported that the prevalence of LBP in US adults aged 20-69 years old was 13.1% [23].…”
Section: Discussioncontrasting
confidence: 59%
“…Second, a prior study on the smoking prevalence of Japanese reported that in 2013, the smoking prevalence of female sales workers was 17.8% (95%CI, 17.0-18.6), which was significantly higher than that of female clerical workers at 9.9% (95% CI, 9.5-10.3) [31]. Prolonged standing [32], workplace violence [33], and smoking [4,21,34] have been identified as risk factors for LBP, which may have led to a higher prevalence of self-reported LBP among Japanese female sales workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, early consultation with a physician is important because musculoskeletal symptoms that become more intense or chronic can lead to decreased work productivity, absence due to sickness,19 and presenteeism (attending work despite health problems) 20. The lifestyle questionnaire was developed in 1994 based on the opinions of physicians and experts involved in health check-ups, and plays an important role as an aid to physicians’ diagnosis and consultation regarding musculoskeletal diseases 21. The lifestyle questionnaire focused on smoking status (never, former and current smoking), alcohol drinking (no drinking, sometimes, every day), good health habits, dietary habits and daily living and activities 21 22.…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiological evidence suggested that LBP was affected by many factors, reporting that self-reported LBP was common among older age groups [12,[18][19][20], widowed or separated individuals [18], people with lower educational level [12,18], people from poorer economic backgrounds [12], drinkers [20], current smokers [6,[18][19][20][21], individuals with sleep problems [12,20,22], and those with medical comorbidities [12,18]. Additionally, unemployment was associated with low socio-economic status (SES), cigarette smoking, heavy drinking, and chronic physical illnesses [23].…”
Section: Covariatesmentioning
confidence: 99%